Wasathiyah dalam Kurikulum PAI Terintegrasi: Sebuah Pendekatan Fenomenologi dan Sosiologi di SD Bina Anak Sholeh Tuban - Hakim, Nur; Miftahuddin, Miftahuddin (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to examine the implementation of wasathiyah (Islamic moderation) values in the integrated Islamic Religious Education (PAI) curriculum through phenomenological and sociological approaches. The research is grounded in the lack of in-depth empirical studies on how teachers and students contextually internalize moderate Islamic values. This study fills the gap in PAI curriculum research, which has largely been normative and textual. Employing a qualitative method with phenomenological and sociological approaches, data were collected through participatory observation, in-depth interviews, and documentation at SD Bina Anak Sholeh Tuban. Data analysis was conducted through reduction, categorization, and interpretation of the participants’ subjective meanings and social dynamics. The findings reveal that wasathiyah values such as tawazun (balance), i’tidal (justice), and tasamuh (tolerance) are not only taught cognitively but are also experienced in real-life learning and social relationships, fostering harmony between spirituality and rationality in everyday life.